Outer membrane vesicles: an attractive candidate for pertussis vaccines - Hozbor, Daniela Flavia (2017)
Pertussis is a current public-health problem and major cause of death in children, even in countries with high vaccination coverage . This bacterial respiratory disease is caused by Bordetella pertussis, but other Bordetella species such as B. parapertussis, B. bronchiseptica, and B. holmesii can provoke symptomatology similar to pertussis. The World Health Organization (WHO) estimated that in 2008, about 16 million cases of pertussis occurred worldwide with about 195,000 deaths, 95% in developing countries.